Analysis of the Principal’s Democratic Leadership Style in State Elementary School 2 Cipanas West Java - Dikdik, Asep; Firyal Fatin Oktaviani; Suryana, Asep; Ulfia Nanda Maulia; Arini Nur Fariha (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This study aimed to ascertain the democratic leadership style of the principal of State Elementary School 2 Cipanas, West Java, Indonesia. This research employed a qualitative approach. In order to collect the requisite data for this study, the researchers employed a combination of techniques, including a literature review, interviews, and observation. The data processing phase was conducted using the ATLAS.ti software. The text-interactive application was employed to facilitate the drawing of conclusions from the interview results and the presentation of the research results. The findings of this study indicate that the democratic leadership style of State Elementary School 2 Cipanas's principal is characterized by a proclivity to engage in deliberations with teachers and education personnel regarding decision-making, a tendency to recognize the potential of members, a disposition to listen to criticism or opinions expressed by members, and a commitment to collaboration with members, particularly in matters pertaining to learning governance, habituation, and related administrative tasks. This study represents a significant contribution to the field of educational research, as it challenges the prevailing trend of focusing on the correlational paradigm alone in the study of principals' democratic leadership. The implications extend beyond the theoretical realm, offering a compelling rationale for the implementation of democratic leadership practices. These practices have the potential to align with specific local contexts, facilitate strategic innovations in educational settings, cultivate a positive school climate, enhance collaboration between principals and teachers, and ultimately improve the quality of the learning process.